HUBUNGAN PARAMETER KUAT TARIK TAK LANGSUNG TERHADAP MODULUS RESILIEN CAMPURAN BERASPAL DINGIN DENGAN ASPAL BUSA - Djoko Widayat (Jurnal Jalan-Jembatan, 2010)
Cold mix recycling with foamed bitumen is a technology alternative which can be implemented in selecting treatment strategy for road rehabilitation project. This construction is an environment friendly and can reduce air emission on road project. Mix material can consist of Reclaimed Asphait Pavement (RAP), virgin aggregate with or without cement addition.The criteria of recycling with foamed bitumen mixture based on value of Indirect Tensile Strength (ITS), Tensile Strength Ratio (TSR) and Unconfined Compressive Strength (UCS). Whereas the mix stiffness is based on Resilient Modulus (MR). The value of ITS and MR is influenced by laboratory testing or field temperature. The result form some specimens which were tested in some temperature variotions shows that the increased of test temperature, the ITS and MR decreased. There is significantly fair correlation between two parameters MR and ITS in power regression type. This prediction can be used as a guide to determine coefficient layer in pavement thickness design. Key word : cold mix recyling, foamed bitumen, RAP, ITS, Resilient Modulus, coefficient layer